Predictive factors of adherence to frequency and duration components in home exercise programs for neck and low back pain: an observational study - Medina-Mirapeix, Francesc (BioMed Central, 2009)
BACKGROUND: Evidence suggests that to facilitate physical activity sedentary people may adhere to one component of exercise prescriptions (intensity, duration or frequency) without adhering to other components. Some experts have provided evidence for determinants of adherence to different components among healthy people. However, our understanding remains scarce in this area for patients with neck or low back pain. The aims of this study are to determine whether patients with neck or low back pain have different rates of adherence to exercise components of frequency per week and duration per session when prescribed with a home exercise program, and to identify if adherence to both exercise components have distinct predictive factors. METHODS: A cohort of one hundred eighty-four patients with chronic neck or low back pain who attended physiotherapy in eight primary care centers were studied prospectively one month after intervention. The study had three measurement periods: at baseline (measuring characteristics of patients and pain), at the end of physiotherapy intervention (measuring characteristics of the home exercise program) and a month later (measuring professional behaviors during clinical encounters, environmental factors and self-efficacy, and adherence behavior). RESULTS: Adherence to duration per session (70.9% ± 7.1) was more probable than adherence to frequency per week (60.7% ± 7.0). Self-efficacy was a relevant factor for both exercise components (p < 0.05). The total number of exercises prescribed was predictive of frequency adherence (p < 0.05). Professional behaviors have a distinct influence on exercise components. Frequency adherence is more probable if patients received clarification of their doubts (adjusted OR: 4.1; p < 0.05), and duration adherence is more probable if they are supervised during the learning of exercises (adjusted OR: 3.3; p < 0.05). CONCLUSION: We have shown in a clinic-based study that adherence to exercise prescription frequency and duration components have distinct levels and predictive factors. We recommend additional study, and advise that differential attention be given in clinical practice to each exercise component for improving adherence.